Hubungan Stres Kerja dengan Kelelahan Kerja Petani Karet di PTPN XII Kebun Renteng, Ajung-Jember - Sari Mulia Ningrum; Erti Ikhtiarini Dewi; Enggal Hadi Kurniyawan (UPT Percetakan dan Penerbitan Universitas Jember, 2020)
Rubber farmers often face heavy workload problems, cold weather, and unsafe environmental conditions that cause job stress and work fatigue. The purpose of the study was to analyze the relationship between job stress and work fatigue of rubber farmers. The study design used observational analytic research with cross-sectional approach and a simple random sampling technique. There were 78 respondents. Data were collected using the job stress questionnaire and the Fatigue Severity Scale (FSS). Data analysis was performed by Spearman-rank Correlation test with a significance level of 0.05. The results showed that from 78 people there were 73 people (92.6%) experienced severe stress. And as many as 78 respondents (100%) experienced high work fatigue. There was a significant relationship between job stress and work fatigue of rubber farmers in PTPN XII Renteng Gardens, Ajung-Jember (p-value 0,000; r = 0.538). A positive relationship meaning the higher of job stress the higher of work fatigue. Farmers were recommended to do relaxation therapy to prevent work fatigue due to work stress.